Dual-wavelength random fiber laser incorporating micro-air cavity - Mohd Yusoff, Norita (2019)
Almost one decade ago, a newborn fiber laser with simplified version called random distributed feedback fiber laser (RDFB-FL) has been a spotlight among the photonic research community. Despite of the natural behavior of Rayleigh scattering as a fundamental loss for propagating light in optical fibers, it can be utilized as a distributed mirror in ultra-long fiber laser. In this case, the mechanism of feedback is termed as random which leads to the development of RDFB-FL. However, the absence of physical feedback devices require a very high power to overcome total cavity losses to be a laser. In this research work, a simple linear cavity half open ended of random fiber laser (HOCRFL) consists of 36 km TrueWave RS fiber (TW) incorporating micro-air cavity (MAC) is proposed. The MAC is constructed by adjusting the air-gap distance between two optical fibers that produce multiple fringes based on the Fabry-Pérot cavity. At the same time, this MAC enhances the reflectivity to improve the overall laser performance. For MAC characterizations, the transmission loss increases while reflectance, transmittance and channel spacing decrease with the increment of air-gap distances. The best MAC location in the fiber laser cavity is at the opposite end of the output port and the optimum pumping configuration of HOCRFL is the bidirectional scheme. From the optimization of MAC air-gap distance from 100 μm to 1000 μm, smaller air-gaps (100 μm to 400 μm) are preferable for high pump power operation near 2 W while larger air-gaps (500 μm up to 1000 μm) are suitable for low pump power operation below 1.5 W. Based on the findings, it is found that the 200 μm and 600 μm air-gap distance produce the best lasing performance for these two separate pump power regions. The former air-gap distance generates dual-wavelength laser at 1552.48 nm and 1557.04 nm with 18.79 dB and 18.73 dB optical signal-to-noise ratio (OSNR), respectively. On the other hand, for the 600 μm air-gap distance, the dual-wavelength lasers occur at 1553.86 nm and 1555.75 nm with 14.69 dB and 13.73 dB OSNR. In comparison between these two air-gap distances, the 200 μm air-gap distance has better OSNR. However, its critical power (pump power that generate the best lasing performance) of 1987 mW is higher than 1240 mW obtained from 600 μm air-gap distance. It is believed that the novelty of this work lies within the use of simple architecture of MAC in linear cavity random fiber laser to dual-emission peak wavelength.